2008
DOI: 10.1103/physrevb.78.193407
|View full text |Cite
|
Sign up to set email alerts
|

Height-dependent nucleation and ideal layer by layer growth in Pb/Pb(111)/Si(111)

Abstract: It has been puzzling why for Pb/Si͑111͒, oscillations have been observed at temperatures as low as 18 K and were found to improve with decreasing temperature. With scanning tunneling microscope we have directly observed this ideal layer by layer growth. A dramatic dependence of the second layer island morphology on island height, expected from quantum size effects ͑QSE͒, is also found. Low density of fractal islands on stable vs high density on unstable Pb islands on a mixed height island confirms the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…This fractal shape is clearly seen in Fig. 3(b) and it is a characteristic of Diffusion-Limited Aggregation (DLA) 32,33 which results from the low mobility of deposited Pb atoms at the experimental growth temperature. All fractal islands are 1 ML high as shown in the line profile (Fig.…”
Section: Shown Inmentioning
confidence: 89%
“…This fractal shape is clearly seen in Fig. 3(b) and it is a characteristic of Diffusion-Limited Aggregation (DLA) 32,33 which results from the low mobility of deposited Pb atoms at the experimental growth temperature. All fractal islands are 1 ML high as shown in the line profile (Fig.…”
Section: Shown Inmentioning
confidence: 89%
“…5. On the Si (111) surface region [4] is very narrow and the 2";3 x 2";3 reconstruction (Fig. 6( c)) is observed in this region [31].…”
Section: Methodsmentioning
confidence: 99%
“…The dangling bond density on the (113) surface is less than that on the (337) which in turn is less than that on the (225) unit [15], and is manifested in the desorption sequence as well. The desorption region around 600°C (region [4]) marks the formation of 2x(337) facet which, owing to the lesser number of dangling bonds, shows comparatively weaker bonding and hence allows faster desorption as compared to the final desorption from the (225) facet (region [5]). Finally above 600°C on (111) and around 850°C on (55 12) surfaces, we retrieve the clean 7 x 7 and 2 xl reconstructions, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and experimental studies indicated that structural and morphological properties of ultrathin Pb films are related to QSE. Minimization of the total internal energy of Pb island with a thickness dependent QSE electronic component leads to the growth of islands with preferential magic thicknesses [10,11,14,[28][29][30][31]. In a continuous layer this minimization manifests itself as a variation of the measured Pb apparent step height (ASH).…”
Section: Introductionmentioning
confidence: 99%